PROBLEM BASED INSTRUCTION SEBAGAI MODEL PEMBELAJARN MATAKULIAH SEMINAR - Ana Rosmiati (Institut Seni Indonesia Surakarta, 2018)
ABSTRACTClassroom Action Research (CAR) is a research model developed by instructors to find out results, problems and solutions to overcome classroom learning. PTK can be a tool to evaluate the results of a learning within a certain period of time. The researcher was interested in conducting PTK in the Department of Visual Communication Design at the Seminar course. The model that will be developed is a based instruction model where students will be taught to solve problems in preparing final assignments using the scientific method. Problems in How the model of applying problem based learning model learning through seminar courses on Visual Communication Design Program students at ISI Surakarta and whether the application of problem based learning learning models can improve students’ ability to complete seminar courses. The purpose of the study was to find a model of the application of problem based learning through Seminar subjects to Visual Communication Design Program students at ISI Surakarta and evaluate the application of problem based learning through seminar courses to improve the ability to prepare final assignments for thesis or work in Visual Communication Design students. in ISI Surakarta. This study uses a type of qualitative research. The research was conducted in the lecture hall of Building 3, Campus II Mojosongo.Keywords: PTK, problem based intruction, model, cycle.ABSTRAKPenelitian Tindakan Kelas (PTK) merupakan salah model riset yang dikembangkan oleh pengajar untuk mengetahui hasil, problematika serta solusi untuk mengatasi pembelajaran di kelas. PTK dapat menjadi alat untuk mengevaluasi hasil dari sebuah pembelajaran yang dalam kurun waktu tertentu. Peneliti tertarik untuk melakukan PTK di mahasiswa Jurusan Desain Komunikasi Visual pada matakuliah Seminar. Model yang akan dikembangkan adalah model based instruction di mana mahasiswa akan diajari menyelesaikan persoalan dalam menyusun tugas akhir dengan menggunakan metode ilmiah. Masalah dalam Bagaimana model penerapan pembelajaran model problem based learning melalui matakuliah seminar pada mahasiswa Progdi Desain Komunikasi Visual di ISI Surakarta dan apakah penerapan model pembelajaran problem based learning dapat meningkatkan kemampuan mahasiswa dalam menyelesaikan matakuliah seminar. Adapun tujuan penelitian adalah adalah menemukan model penerapan pembelajaran problem based learning melalui matakuliah Seminar pada mahasiswa Progdi Desain Komuniasi Visual di ISI Surakarta dan mengevaluasi penerapan pembelajaran problem based learning melalui matakuliah seminar dapat meningkatkan kemampuan menyusun tugas akhir baik skripsi atau karya pada mahasiswa Progdi Desain Komunikasi Visual di ISI Surakarta.Penelitian ini menggunkan jenis penelitian kualitatif Penelitian dilakukan di Ruang kuliah Gedung 3 Kampus II Mojosongo.Kata kunci : PTK, problem based intruction, model, siklus.